KEMAJUAN TEKNOLOGI DAN POLA HIDUP MANUSIA DALAM PERSPEKTIF SOSIAL BUDAYA - Muh David Balya Al (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Writing articles aims to: (1) determine changes in human life patterns due to technological advances, (2) determine the influence of technological advances in the socio-cultural field, and (3) find out solutions in overcoming the negative impacts of technological advances. The research method used in this writing is literature study which originates from books, articles, journals, and is complemented by survey results regarding the use of modern technology used as a data collection technique. The data obtained was analyzed descriptively critically by the authors using the socio-cultural change theory approach. The results of the discussion in this paper show that technological advances continue to develop very rapidly and give birth to a digital society, there are changes in human life patterns due to technological advances so that they become more pragmatic, hedonic, isecular, and give birth to instant generations but also save effectiveness and efficiency in behavior and actions. technological progress has a double face because it creates positive and negative influences on human life and efforts to suppress and overcome the negative impacts of technological progress can be carried out by synergizing the roles of the family, education, society and the state.